The influence of feeding crimped kernel maize silage on broiler production, nutrient digestibility and meat quality. Issue 1 (2nd January 2016) - Ranjitkar, S.; Karlsson, A.H.; Petersen, M.A.; Bredie, W.L.P.; Petersen, J.S.; Engberg, R.M.
Abstract: Two experiments were carried out in parallel with male Ross 308 broilers over 37 d. An experiment with a total of 736 broilers was performed to study the effect of dietary inclusion of crimped kernel maize silage (CKMS) on broiler production and meat quality. Another study with 32 broilers was carried out from 21 to 25 d to investigate the inclusion of CKMS on nutrient digestibility. In both trials, 4 dietary treatments were used: wheat-based feed (WBF), maize-based feed (MBF), maize-based feed supplemented with 15% CKMS (CKMS-15) and maize-based feed supplemented with 30% CKMS (CKMS-30). Compared with MBF, the dry matter (DM) intakes of broilers receiving CKMS-15 and CKMS-30, respectively, were numerically 7.5 and 6.2% higher and feed conversion ratio 6 and 12% poorer (significant for 30% CKMS), although there were no significant differences in AME content between the three diets. At 37 d, the body weight of birds receiving 15% CKMS was similar to birds fed with MBF. However, the inclusion of 30% CKMS decreased broiler growth. Dietary supplementation with CKMS significantly reduced the apparent digestibility of phosphorus. The fat digestibility was significantly lower for CKMS-30 than for the other three diets. Broiler mortality decreased significantly when CKMS was added to the diet. The consumption of drinking water was significantly lower in all maize-based diets as compared to WBF and was lowest in broilers fed with CKMS-30. An improved litter quality in terms of DM content and a lower frequency of foot pad lesions was observed with broilers supplemented with both dietary levels of CKMS. The addition of CKMS to maize-based diets increased juiciness, tenderness and crumbliness of the meat. In conclusion, the dietary supplementation of 15% CKMS had no negative effect on broiler growth and positively influenced bird welfare in terms of mortality and foot pad health. Therefore, the addition of 15% CKMS to maize-based diets is considered an advantageous feeding strategy in broiler production.